Massive versus lightweight building: the latest investigations of (ecological) sustainability assessment: Massivbau versus Leichtbau: Neueste Untersuchungen zur (ökologischen) Nachhaltigkeitsbewertung. Issue 1 (February 2017) - Pohl, Sebastian; Graubner, Carl‐Alexander
Abstract: Over recent years, the authors have released various research findings concerning the sustainability of masonry construction for detached houses [1] and apartment buildings [2] in comparison with alternative construction methods (timber, reinforced concrete). Meanwhile, in cooperation between the Institute for Concrete and Masonry Structures, TU Darmstadt, and its spinoff LCEE Life Cycle Engineering Experts, these analyses have been merged to a further study with increased consideration of all relevant construction methods for multi‐floor residential buildings; preliminary results have already been presented in this journal [3]. The following paper now shows the final findings including data updates, added construction variants (imported timber scenario) and extended life cycles (50 and 80 years).